A parallel algorithm for generating chain code of objects in binary images - Chia, Tsorng-Lin; Wang, Kuang-Bor; Chen, Lay-Rong; Chen, Zen (Information sciences, 2003)
This paper addresses parallel execution of chain code generation on a linear array architecture. The contours in the proposed algorithm are viewed as a set of edges (or contour segments) that can be traced by a top-down contour tracing method to generate the chain codes for the outer and inner object contours. A parallel algorithm that contains the chain code generating rules and operations needed is also described, and the algorithm is mapped onto a one-dimensional systolic array containing ⌈ 1 2 (N+1)⌉ processing elements (PEs) to devise this architecture. The architecture extracts the contours of objects and quickly generates the corresponding chain codes after the image data in all rows are inputted in a linear fashion. The total processing time for generating the chain codes in an N× N image is O(3 N). By doing so, the real-time requirement is fulfilled and its execution time is independent of the image content. In addition, a partition method is developed to process an image when the parallel architecture has a fixed number of PEs; say two or more. The total execution time for an N× N image by employing a fixed number of PEs is N( N+1)/ M+2( M−1), when M is the fixed number of PEs.